Adalimumab Therapy in Children With Crohn Disease Previously Treated With Infliximab. Issue 2 (February 2015) - Cozijnsen, Martinus; Duif, Vera; Kokke, Freddy; Kindermann, Angelika; van Rheenen, Patrick; de Meij, Tim; Schaart, Maaike; Damen, Gerard; Norbruis, Obbe; Pelleboer, Rolf; Van den Neucker, Anita; van Wering, Herbert; et al.
ABSTRACT: Objectives: Adalimumab, a humanised anti-tumour necrosis factor antibody, is an effective treatment in adult patients with refractory Crohn disease (CD). The available literature on its efficacy in children remains limited. We aimed to evaluate the real-world efficacy in paediatric patients with CD and compare the efficacy between infliximab (IFX) nonresponders and patients who lost response to IFX. Methods: All Dutch patients with CD receiving adalimumab before the age of 18 years after previous IFX therapy were identified. We analysed longitudinal disease activity, assessed by the mathematically weighted Pediatric Crohn's Disease Activity Index (wPCDAI) or the physician global assessment (PGA), and adverse events (AEs). Results: Fifty-three patients with CD were included. Twelve patients received monotherapy and the others received combination treatment with thiopurines (n = 21), methotrexate (n = 11), steroids (n = 7), or exclusive enteral nutrition (n = 2). Median follow-up was 12 months (interquartile range 5–23). Remission was reached in 34 patients (64%, wPCDAI < 12.5 or PGA = 0) after a median of 3.3 months, and maintained by 50% for 2 years. Eleven patients (21%) reached response but not remission (decrease in wPCDAI ≥ 17.5 or decrease in PGA). Eighteen patients (34%) failed adalimumab treatment because of nonresponse (n = 4), lost response (n = 11), or AEs (n = 3). More IFX nonresponders failed adalimumab treatment than patients who lost response to IFX (2/3 vs 8/34, hazard ratio 18.8, 95% confidence interval 1.1–303.6). Only 1 patient encountered a serious AE, a severe but nonfatal infection. Conclusions: In clinical practice, adalimumab induces remission in two-thirds of children with IFX refractory CD.